ANALISIS SIFAT TANAH PADA LAHAN PADI SAWAH DI NAGARI PAKAN RABAA DI KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - Maivanorita, Maivanorita; Dasrizal, Dasrizal; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
The aims of this research are 1) to know the characteristics of physics land (Tekstur, drainage, permeabilitas) to the rice paddy land, 2) to know the characteristics of chemistry land ( pH, element of N, element of P and element K) to the rice paddy land, 3) to know the characteristics of biology land (organic materials) to the rice paddy land. Set of farm exist in research area consisted of 31 set of and farm of sample taken only 4 set of farm.The technique of took sample is stratified random sampling, that is a technique withdrawal of taken sample is strata (Level) set of farm. The data analysis that used is descriptive, that is analysis inform the comparison tables between characteristics of land (tekstur, permeabilitas, drainase, pH, nitrogen element, phosporus element, pottasium element and organic materials campared to the level suitability of the rice paddy land.Result of the research are: 1) the nature of land fisics (tesktur, permeabilitas, and drainage) to rice field farm in the Pakan Rabaa distric of colossal Koto Parik Gadang Diateh Sub-Province of South Solok, The have tesktures , drainase, permeabilitas, include in categories middle and good for rice farm. 2) the nature chemistry of land fisics (pH, element of N, element of P and element K) at rice field farm in the Nagari Pakan Rabaa District Of Colossal Koto Parik Diateh Sub-Province of South Solok, owning pH, nitrogen element, potassium element pertained categories middle and goodness, while element of posfor pertained bad category for the crop of 3) Nature of land;ground biology (organic materials) at rice field paddy farm paddy inNagari the Pakan Rabaa District Of Colossal Koto Parik Diateh Sub-Province of South Solok owning organic materials content in category good to paddy crop.